The Physical, Physiological Quality and Biochemical Content of Trema (Trema orientalis Linn.Blume) Based on Maturity Level - Naning Yuniarti; Rina Kurniaty; NFN Danu; Nurmawati Siregar (Jurnal Perbenihan Tanaman Hutan, 2016)
Trema orientalis L. Blume is a multipurpose plant for all parts of the tree can be used. In order to support the successful development of this plant, seed quality is required, in which one of the requirements for determining quality seed is the seed should come from physiologically fruit mature. The research objective was to determine the quality of the physical, physiological quality, and a biochemical content (fat, carbohydrate and protein) of trema seed based on of fruit maturity. Trema seed used in this research comes from Badung regency, Bali Province. Trema fruit grouped into three color level (green, brown, black). The research design used is CRD (completely randomized design) with a treatment rate of fruit color. Parameters were observed ie. fruit and seed size, the weight of the fruit and seeds, fruit and seed moisture content, content of biochemistry (protein, fat, carbohydrates), germination and speed germination. The results showed: (1) The level of maturity of the fruit significantly affects the physical quality (size of fruit and seeds, fruit weight and seed, the water content of fruits and seeds), physiological (germination, speed of germination), and the content of biochemistry (fats, carbohydrates, protein) trema seed, (2) Quality of physical and physiological seed that comes from the fruit of the black better than the green and chocolate fruit, (3) the content of fats, carbohydrates and protein of trema seed differ for each level of maturity (green, brown, black), (4) Fruit Trema reaching physiological maturity is the fruit of the black with criteria that is : long fruit 3,87 ± 0,05 mm and width 3,41 ± 0,02 mm; long seed 2,10 ± 0,05 mm and width 1,81 ± 0.06 mm; 1000 grain weight of fruit 25.6883 grams; 1000 grain weight of seed 3.8288g; moisture content of fruit 54,74%; moisture content of seed 12,03%; percentage germination 78%; speed of germination 3,05% / Etmal; content of carbohydrate 20,10%; content of protein 2,84% and content of fat 0,65%.